REPRESENTATION OF IRONY IN WHATSAPP GROUP CHAT - Anna Riana Suryanti Tambunan; Fauziah Khairani Lubis; Winda Setia Sari; Widya Andayani; Moh Hilman Fikri (Lire Journal (Journal of Linguistics and Literature), 2023)
This article explores the representation of irony in WhatsApp Group chats, aiming to identify the types of irony and narrate the meaning of the irony used. A case study was geared under Perrine's (1966) and Leech's (1981) analysis of the type of irony. Moreover, the result disclosed that touches of sarcasm were the favorable choice of irony to express the participants’ feelings. Sarcasm was detected by using uppercase characters, exclamation marks, and teasing words. Hyperbole and understatement were the second participants’ favorite to use to exaggerate reality and make a dramatic situation. Furthermore, implementing irony in daily conversation with decent knowledge is significant to flourish and enrich their linguistic adequacy to avoid misunderstanding and know the appropriate situation manual students' exploitations of irony will.